Evaluasi Pelaksanaan Penggunaan Bantuan Operasional Sekolah Daerah Tahun Anggaran 2020 dengan Model CIPP (Studi Kasus Pada Smk Negeri Se-Kota Denpasar) - Y. Sutrisnawati; I.G.K.A Sunu; K.R. Dantes (Jurnal Administrasi Pendidikan Indonesia, 2021)
The aim of the study was to investigate the evaluation results separately or together on context, input, process, product and constraints that occur in the implementation of the use of BOSDA Fiscal Year 2020 at smk negeri in Denpasar. The present research used a program evaluation research with CIPP model. There were 26 people and the whole acted as population and used as a research sample using saturated sample techniques. Data context, input, process, product collected by questionnaire using Likert scale 1-5. In this study using descriptive quantitative analysis method. To determine the effectiveness of implementing bosda's usage, the raw score is transformed into Z-score then into T-Score then verified into Glickman Quadrant. The results in this study are: 1) Effectiveness of bosda usage implementation reviewed from context obtained negative results (-), 2) Effectiveness of implementation of bosda use reviewed from inputs obtained negative results (-), 3) Effectiveness of bosda usage implementation reviewed from the process obtained effective results (+), 4) Effectiveness of implementation of bosda use reviewed from product obtained effective results (+), 5) Evaluation results together against the implementation of bosda use reviewed from i context, input, process, product obtained less effective results (- - + +), and 6) Obstacles faced in the use of BOSDA is there is a discrepancy in the use of BOSDA with government policy, lack of readiness from bosda managers, lack of clarity from the legal basis of the use of BOSDA.